Characterization of different Moroccan sands to explain their potential negative impacts on CSP solar mirrors. (December 2019) - Pescheux, Anne-Claire; Le Baron, Estelle; Raccurt, Olivier
Highlights: Sand analyzing is a key point to reduce the cost of energy and maintenance of a CSP plant. Geographical location determines the nature of degradation and soiling effect. 90% of the sand particles are very coarse which can damage the CSP mirrors. The degradation of the mirror surface depends on the shape and the hardness of the particles. The combination of the sand particles and the local wind speed determines the gravity of the damages. Abstract: During the life-time of Concentrated Solar Power (CSP) plants, optical performance of solar mirrors are affected by soiling phenomenon and surface degradations, especially in desert and oceanic environments such as those prevailing in North Africa. This optical loss results from the deposition of dust particles, salts, organic materials or any other contaminants present in the solar field or around the CSP installation sites. This phenomenon depends on the different exposure sites with every location having its own meteorological and geological characteristics. Moroccan CSP sites are planned in many locations with different environmental conditions: arid, semi-arid and Saharan, with or without oceanic influence. These environmental factors can have an aggressive impact on the CSP mirrors. Indeed, large particles will tend to degrade the mirror by scratching or breaking the glass surface, while small particles have more chance to deposit on solar mirrors and thus create a soiling layer. These particles are generated from many sources (sand storm, pollution, vehicular movements, etc.) and are transported through the air. This mode of transport is determined as a function of mineral, size, shape and hardness. In this paper, we present a simple methodology for analyzing the chemical and physical characteristics of the sand particles, characterization techniques, and their appropriate laboratory equipment. All the factors previously mentioned could be critical for the CSP mirrors. That is why analyzing these data may be a key point for the industry to understand the effects of soiling and degradation on the CSP mirrors in order to increase the global economic profitability of their solar plants.